The Role of Social Media on Customer Satisfaction in Gen Z : A Case Study of Subang Regency - Indriani Jusuf, Dewi; Mochamad Ramdan, Andry (Yayasan Pendidikan Belajar Berdikari, 2024)
This study aims to analyze the role of social media usage on Customer Satisfaction skills of Gen Z in Subang Regency. This study uses a quantitative method with a survey approach. The research sample consisted of 92 randomly selected Gen Z. Data were collected through a questionnaire that measured the frequency, duration, type, and purpose of social media use and interpersonal communication skills. The results of multiple regression analysis showed that the frequency of social media use (B = 0.432, p < 0.001), duration of social media use (B = 0.298, p < 0.01), type of social media used (B = 0.215, p < 0.05), and purpose of social media use (B = 0.148, p < 0.05) all have a positive and significant role in interpersonal communication skills. The resulting regression model has a coefficient of determination (R²) of 0.572, indicating that 57.2% of the variability in Customer Satisfaction skills can be explained by the independent variables used in this study. The findings indicate that social media usage significantly influences Gen Z’s Customer Satisfaction skills. The frequency of social media usage plays the biggest role, followed by the duration, type, and purpose of social media usage. Therefore, it is important for Gen Z to use social media wisely in order to improve their Customer Satisfaction skills.